Stroke: challenge for managers in the health care network - Camila Pinno; Jucelaine Arend Birrer; Aline Amaral dos Santos; Ana Paula Flores Colpo; Andréia Claro Tavares; Fernanda Vianna Schmitt (Universidade Federal de Santa Maria, 2015)
Doi: 10.5902/2179769213768 Objective: to identify the healthcare network for users affected by stroke in a city in the central region of Rio Grande do Sul/Brazil. Method: qualitative, exploratory research. The subjects of the study  were six managers of public services of health care of the city. The data collection was conducted between October and December of 2013 through semi-structured interviews. The data were analyzed by Thematic Content Analysis. Results: two categories, which were not a priori, were defined: Health Care Networks and Comprehensive Care. Conclusion: the findings demonstrate that the tools or devices to the effective care of users affected by stroke are not utilized due to managers' lack of knowledge on the work processes, leading to the fragmentation of care and to the non-shared management.